Gas Chromatography Mass Spectroscopy (GCMS) Qualitative Analysis for Morphine, Heroin and Codeine used in Doping - Ayu Nala El Muna Haerussana; Mimin Kusmiyati; Irvan Herdiana (Universitas Tidar, 2023)
Three types of doping drugs, morphine, heroin, and codeine were analyzed qualitatively in urine using GCMS: HP5MS column containing a nonpolar substance, phenylmethyl siloxane, with a temperature range of 90-250ºC and a rate of increase of 10ºC/minute. Diethyl ether was used to extract morphine, codeine, and heroin. The extractions were performed at pH 8, the organic phase was evaporated, followed by derivatization. Morphine and its derivatives were treated with a solution of N-methyl-N-trimethylsilyl-trifluoroacetamide and N-methyl-bis-trifluoroacetamide. The results of the gas chromatographic analysis showed that the retention times of morphine, heroin, and codeine the retention times were 8.01, 7.32, 6.21 minutes, while those of their derivatives were 8.10, 8.10, 7.95 minutes respectively. The identification of each drug using mass spectrometry revealed that their mass spectra were identical to the standard. The mass spectra of the derivatives: morphine-TMS and codeine-TMS showed a resemblance index of 93% respectively compound to the standard, with a detection limit of 2 ug/ml.